A review study on diesel and natural gas and its impact on CI engine emissions - Alrazen, Hayder Abdullah Luaibi; Ahmad, Kamarul Arifin (Universiti Putra Malaysia Press, 2017)
Diesel engines produce high emissions of nitrogen oxide, smoke and particulate matter. The challenge is to reduce exhaust emissions but without making changing their mechanical configuration. This paper is an overview of the effect of natural gas on the diesel engine emissions. Literature review suggests that engine load, air-fuel ratio, and engine speed play a key role in reducing the pollutants in the diesel engine emissions with natural gas enrichment. It is found that increasing the percentage of natural gas (CNG) will affect emissions. Nitrogen oxide (NOx) is decreased and increased at part loads and high loads respectively when adding CNG. The reduction in carbon dioxide (CO2), particulate matter (PM) and smoke are observed when adding CNG. However, carbon monoxide (CO) and unburned hydrocarbon (HC) are increased when CNG is added.